2018
DOI: 10.1542/peds.2017-1549
|View full text |Cite
|
Sign up to set email alerts
|

Improving Time to Antibiotic Administration for Bone Marrow Transplant Patients With First Fever

Abstract: Implementation of a standardized process for notifying providers of new fever in patients, prioritization of antibiotic preparation in the central pharmacy, and timely antibiotic order entry resulted in improved times to antibiotic administration in the febrile bone marrow transplant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…There are several publications on the standardization of timely antibiotic administration in pediatric immunocompromised patients in the emergency room 14-16 or inpatient settings 9,10 using QI methodology. One recent study from a large children's hospital showed improvement from 35% to 65% for patients receiving antibiotics within 60 minutes of fever if there was a fever contingency plan in the daily progress note.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several publications on the standardization of timely antibiotic administration in pediatric immunocompromised patients in the emergency room 14-16 or inpatient settings 9,10 using QI methodology. One recent study from a large children's hospital showed improvement from 35% to 65% for patients receiving antibiotics within 60 minutes of fever if there was a fever contingency plan in the daily progress note.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another large children's hospital study reported sustained improvement in administration of antibiotics >90% of the time at their bone marrow transplantation unit. 10 Interventions that led to improvement were establishing standardized processes for provider notification and timely antibiotic ordering, and prioritization of antibiotic preparation at the pharmacy. These processes were less important at our center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation